Research ethics oversight in Norway: structure, function, and challenges - R. Froud; T. J. Meza; K. O. Ernes; A. M. Slowther (BMC, 2019)
Abstract Background While the development and evaluation of clinical ethics services in Norway has been recognized internationally, the country's research ethics infrastructure at times may have been less well developed. In 2016, media interest in the controversial nature of some health services research and pilot studies highlighted gaps in the system with certain types of research having no clear mechanisms through which they may be given due independent consideration. It is not clear that new legislation, implemented in 2017, will address this problem. Summary We explore relevant law, committee scope, and the function of the system. We show that 1) Norwegian law provides for ethics assessment for all forms of health research; 2) regional RECs in Norway might not have always enforced this provision, considering some interventional health services research to be outside their remit; and 3) Norwegian law does not explicity provide for local/university RECs, meaning that, in practice, there may be no readily accessible mechanisms for the assessment of research that is excluded by regional RECs. This may include health services research, pilot studies, and undergraduate research. New 2017 legislation has no effect on this specifically but focuses on institutions regulating researcher activity. This may place researchers in the difficult situation of on one hand, needing to hold to recognized ethical standards, while on the other, not readily having access to independent committee scrutiny to facilitate consistent operation with these standards. Conclusion To support researchers in Norway and to protect the public, it may be necessary either to widen the regional RECs' remit or to make legislative alterations that permit and do not discourage the existence of local RECs.